2018
DOI: 10.3892/ol.2018.9419
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of nuclear magnetic resonance spectroscopy to identify salivary metabolite alterations in patients with head and neck cancer

Abstract: The analysis of the salivary metabolomic profile may offer an early phase approach to assess the changes associated with a wide range of diseases including head and neck cancer. The aim of the present study was to investigate the potential of nuclear magnetic resonance (NMR) spectroscopy for detecting the salivary metabolic changes associated with head and neck squamous cell carcinoma (HNSCC). Unstimulated whole-mouth saliva samples collected from HNSCC patients (primary tumour was located either in the larynx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 47 publications
0
49
0
Order By: Relevance
“…Nuclear magnetic resonance (NMR) spectroscopy can detect and measure metabolites in a solution with minimal sample preparation. This quantitative technique is based on the magnetic properties of atomic nuclei [31]. Each compound has a characteristic resonance frequency that makes it easy to distinguish.…”
Section: Metabolomementioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear magnetic resonance (NMR) spectroscopy can detect and measure metabolites in a solution with minimal sample preparation. This quantitative technique is based on the magnetic properties of atomic nuclei [31]. Each compound has a characteristic resonance frequency that makes it easy to distinguish.…”
Section: Metabolomementioning
confidence: 99%
“…The Authors found two metabolites, fucose and 1,2-propanediol, to be significantly upregulated, whereas proline was significantly downregulated in patients affected by HNSCC. The combination of four salivary metabolites (fucose, glycine, methanol, and proline) together provided maximum discrimination among HNSCC patients and healthy controls [31]. The role of fucosylation of glycoproteins in the development of cancer has been studied in recent years [89].…”
Section: Oral Cancermentioning
confidence: 99%
“…These include the small amount of sample needed compared with other volume average techniques, as well as the swiftness of the experimental data acquisition that can be performed in as fast as a few minutes [21]. The amount of saliva supernatant used for NMR analysis ranged from 0.17 to 0.60 mL (Table 1A) [3][4][5][6][7][8][9][10][11][12][13][14][15]. A saliva sample does not need any complex pre-treatment or preparation for the solution state NMR analysis to be performed [17].…”
Section: The Role Of Nuclear Magnetic Resonance In Saliva Testing Andmentioning
confidence: 99%
“…A saliva sample does not need any complex pre-treatment or preparation for the solution state NMR analysis to be performed [17]. Specifically, the NMR saliva sample preparation consists of centrifugation, and subsequent addition of a NMR solvent, standard, and buffer to the supernatant inside an NMR tube [3][4][5][6][7][8][9][10][11][12][13][14]. On the contrary, the more popular mass spectroscopic analysis requires multiple and more complex sample preparation steps (e.g., extraction, purification, digestion, separation), as well as costly labelling reference compounds for data acquisition and analysis.…”
Section: The Role Of Nuclear Magnetic Resonance In Saliva Testing Andmentioning
confidence: 99%
See 1 more Smart Citation